Analisis Cara Pengajaran Dosen Terhadap Motivasi Belajar Mahasiswa Program Diploma Pelayaran Universitas Hang Tuah Surabaya - Khusniawati, Faulina (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2019)
This study aims to determine the effect of lecturer teaching methods on Student Learning Motivation at the Program Diploma Pelayaran, Universitas Hang Tuah Surabaya. The data analysis technique used is simple regression analysis with a sample of 100 people. From the results of this study it was found that lecturer teaching method (x) significantly influenced student motivation (y) where the constant was 2.815 and the regression coefficient was 0.34. Regression coefficient means that if the value of the lecturer teaching method (x) increases by one unit, the value of the motivational variable (y) will increase by 0.34 assuming the value of the other independent variables does not change or remain constant. The level of significance in the hypothesis test is 0,000 with the decision to reject Ho, so it can be concluded that the teaching method of the lecturer has a positive influence on student motivation within the Program Diploma Pelayaran, Universitas Hang Tuah Surabaya.